A major role for RCAN1 in atherosclerosis progression - Méndez Barbero, Nerea; Esteban, Vanesa; Villahoz, Silvia; Escolano, Amelia; Urso, Katia; Alfranca, Arántzazu; Rodríguez, Cristina; Sánchez, Susana A.; Osawa, Tsuyoshi; Andrés, Vicente; Martínez González, José; Minami, Takashi; et al. (My University, 2013)
Atherosclerosis is a complex in¿ammatory disease involving extensive vascularvessel remodelling and migration of vascular cells. As RCAN1 is implicated in cellmigration, we investigated its contribution to atherosclerosis. We show RCAN1induction in atherosclerotic human and mouse tissues. Rcan1 was expressed inlesional macrophages, endothelial cells and vascular smooth muscle cells andwas induced by treatment of these cells with oxidized LDLs (oxLDLs). Rcan1regulates CD36 expression and its genetic inactivation reduced atherosclerosisextension and severity in Apoe / mice. This effect was mechanistically linked todiminished oxLDL uptake, resistance to oxLDL-mediated inhibition of macro-phage migration and increased lesional IL-10 and mannose receptor expression.Moreover, Apoe / Rcan1 / macrophages expressed higher-than-Apoe / levelsof anti-in¿ammatory markers. We previously showed that Rcan1 mediatesaneurysm development and that its expression is not required in haematopoieticcells for this process. However, transplantation of Apoe / Rcan1 / bone-marrow (BM) cells into Apoe / recipients confers atherosclerosis resistance. Ourdata de¿ne a major role for haematopoietic Rcan1 in atherosclerosis and suggestthat therapies aimed at inhibiting RCAN1 expression or function mightsigni¿cantly reduce atherosclerosis burden